A Comparative Approach to the Study of Dopamine and Male Sexual Behavior: What Can Japanese Quail Teach Us? A Reply to Pfaus (2010) - Kleitz-Nelson, Hayley K.; Dominguez, Juan M.; Ball, Gregory F. (Behavioral Neuroscience, 2010)
One of the most robust findings about dopamine (DA) is that the stimulation of dopaminergic systems promotes the activation of male sexual behavior. The commentary by Pfaus (2010) included a thorough review of studies of DA and male sexual behavior. We agree with him that the release of DA in the preoptic region in male quail in response to females and in association with the exhibition of male sexual behavior appears to be highly conserved and that it seems to have evolved very early in the evolutionary history of the vertebrate brain. However, additional data have been collected indicating that there may be significant species differences in the dopaminergic regulation of male behavior in quail compared with rats. In this response, we take the opportunity to make a few broader points about DA and male sexual behavior in light of other studies that have been conducted in birds and introduce some interesting taxonomic variation that is still not well understood. Reprinted by permission of the publisher.